Identification of catalytic and non‐catalytic activity inhibitors against PRC2‐EZH2 complex through multiple high‐throughput screening campaigns. (25th May 2020) - Zhou, Yan; Du, Dao‐Hai; Wang, Jia; Cai, Xiao‐Qing; Deng, Alicia X.; Nosjean, Olivier; Boutin, Jean A.; Renard, Pierre; Yang, De‐Hua; Luo, Cheng; Wang, Ming‐Wei
Abstract: Enhancer of zeste homolog 2 (EZH2) is the catalytic subunit of the polycomb repressive complex 2 (PRC2) along with embryonic ectoderm development (EED) and suppressor of zeste 12 (SUZ12), which implements transcriptional repression mainly by depositing trimethylation marks at lysine 27 of histone H3 (H3K27me3). Its catalytic activity is closely correlated with the stability of PRC2, and somatic activating mutation of EZH2 Y641F within the catalytic SET domain drives tumor aggressiveness, drug resistance, and poor prognosis. Here, we report two high‐throughput screening (HTS) campaigns targeting EZH2 Y641F and EZH2‐EED interaction, respectively. For the EZH2 Y641F mutant, the HTS campaign involved a library of 250, 000 compounds using a homogenous time‐resolved fluorescence (HTRF) assay and identified 162 hits, while 60, 160 compounds were screened against EZH2‐EED interaction with a fluorescence polarization (FP) assay resulting in 97 hits. Among the 162 EZH2 Y641F inhibitors, 38 also suppressed EZH2‐EED interaction and 80 showed inhibitory effects on the wide‐type (WT) EZH2. Meanwhile, 10 of the 97 EZH2‐EED interaction inhibitors were active against WT EZH2. These hit compounds provide useful tools for the development of novel PRC2‐EZH2 inhibitors targeting its catalytic and non‐catalytic activities. Abstract : Two high‐throughput screening (HTS) campaigns against EZH2 Y641F and EZH2‐EED interaction were performed to discover novel and selective EZH2 inhibitors targeting both catalytic and non‐catalytic activities. One hundred and sixty‐two (162) hits, mostly with reversible and non‐SAM‐competitive properties, were identified in the HTS against EZH2 Y641F from a library of 250, 000 compounds, while 60, 160 compounds were screened against EZH2‐EED interaction that resulted in 97 hits. Crossover examination on these hits found that 38 of the 162 EZH2 Y641F inhibitors also suppressed EZH2‐EED interaction and 80 of them showed inhibitory effects on the wild‐type (WT) EZH2; that is, 16 hits are active on the three targets studied. Meanwhile, 10 of the 97 EZH2‐EED interaction inhibitors were active against wild‐type EZH2. Our findings offer valuable tools to study PRC2‐EZH2 complex.